Enhanching Vocational Students Critical Thinking Skill on Math Logic - Intan Kertiyani, Ni Made; Dita Oktavihari (Griya Journal of Mathematics Education and Application, 2025)
This study aims to analyze differences in the critical thinking skills of vocational high school (SMK) students who study using problem-based learning (PBL)-based modules and school textbooks and vocational students who study using conventional methods assisted by school textbooks. This research is a quasi-experiment research. The research subjects were 76 students at one of the Vocational Schools in Mataram City. The instruments used were tests of critical thinking skills and interview guidelines. The critical thinking ability indicators used combine the critical thinking ability indicators from Ennis and Facione, namely explaining the answer with appropriate reason, justify the quality of argument, justify the relevancy of data and asking appropriate question. The data from the critical thinking skills test were tested using the T-test and the Mann Whitney U-test. The results of this study are 1) there are differences in critical thinking skills between vocational students who study using PBL-based modules and school textbooks and vocational students who learn using conventional methods assisted by school textbooks, 2) there are differences in critical thinking abilities in explaining the answer with appropriate reason and asking appropriate question between SMK students who study using PBL-based modules and school textbooks and SMK students who study using conventional methods assisted by school textbooks.